Investigating Λ baryon production in 𝑝-Pb collisions in jets and the underlying event using angular correlations - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Grünwald, Nadine; Nath, Abhishek; Pachmayer, Yvonne C.; et al. (Physical review, 2025)
First measurements of hadron-Λ (ℎ−Λ) azimuthal angular correlations in 𝑝-Pb collisions at √𝑠𝑁⁢𝑁 =5.02 TeV using the ALICE detector at the Large Hadron Collider are presented. These correlations are used to separate the production of associated Λ baryons into three different kinematic regions, namely those produced in the direction of the trigger particle (near side), those produced in the opposite direction (away side), and those whose production is uncorrelated with the jet axis (underlying event). The per-trigger associated Λ yields in these regions are extracted, along with the near- and away-side azimuthal peak widths, and the results are studied as a function of associated particle 𝑝T and event multiplicity. Comparisons with the dpmjet event generator and previous measurements of the 𝜙⁡(1020) meson are also made. The final results indicate that strangeness production in the highest multiplicity 𝑝-Pb collisions is enhanced relative to low multiplicity collisions in both the jetlike regions and the underlying event. The production of Λ relative to charged hadrons is also enhanced in the underlying event when compared to the jetlike regions. Additionally, the results hint that strange quark production in the away-side of the jet is modified by soft interactions with the underlying event.
Gesehen am 10.09.2025
*ALICE Collaboration: S. Acharya, V. Anguelov, A. Berdnikova, L. Bergmann, A.G. Borquez Carcamo, M.C. Danisch, V.J.G. Feuillard, I. Fokin, P. Glässel, N.A. Grunwald, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, F. Schlepper, J.J. Seo, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, C.A. van Veen, B. Windelband, A. Yuncu, F. Zanone [und 1055 weitere Personen]